A comparative study of the existing conditions of the interiors of a private and public center for street children in MM - Ang Gobonseng, Delia T.; Mayo, Adelaida Villaraza (1995.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Research paper (ID 199)--University of the Philippines, Diliman.
Keywords: Interior decoration -- Philippines -- Manila Metropolitan Area